Cardiovascular autonomic and peripheral sensory neuropathy in women with obesity - Keller, Nóra; Zádori, János; Lippai, Balázs; Szöllősi, Dalma; Márton, Virág; Wellinger, Károly; Lada, Szilvia; Szűcs, Mónika; Menyhárt, Adrienn; Kempler, Péter; Baczkó, István; Várkonyi, Tamás; et al. (Frontiers in Endocrinology, 2024)
Introduction A higher incidence of neural dysfunction in people with obesity has been described. We determined the prevalence of neuropathic lesions in obese women and evaluated their potential association with anthropometric and laboratory parameters. Patients and methods In our cross-sectional study, we enrolled female patients with obesity and without diabetes before obesity treatment. Voluntary female subjects were controls with a normal body mass index (BMI). Autonomic function was assessed by Ewing’s cardiovascular reflex tests, while comprehensive peripheral neuropathic assessments were conducted utilizing the Neurometer®, Tiptherm®, Monofilament®, and Rydel-Seiffer tuning fork tests. Sudomotor function was assessed by the Neuropad®-test. Body composition was examined using the InBody 770. Results 71 patients (mean ± SD; age: 36.1 ± 8.3 years; BMI: 40.2 ± 8.5 kg/m2) and 36 controls (age: 36.4 ± 13.3 years; BMI: 21.6 ± 2.1 kg/m2) were enrolled. Patients had significantly higher systolic (patients vs. controls; 137.5 ± 16.9 vs. 114.6 ± 14.8 mmHg, p<0.001) and diastolic (83.0 ± 11.7 vs.69.8 ± 11.2 mmHg, p<0.001) blood pressure compared to controls. Among autonomic tests, only the heart rate response to Valsalva maneuver (Valsalva-ratio) revealed significant impairment in patients (1.4 ± 0.2 vs. 1.7 ± 0.4, p<0.001). Neurometer® at the median nerve revealed increased current perception threshold (CPT) values at all stimulating frequencies in patients (CPT at 2000 Hz: 204.6 ± 70.9 vs. 168.1 ± 66.9, p=0.013; 250 Hz: 84.4 ± 38.9 vs. 56.5 ± 34.8, p<0.001; CPT at 5 Hz: 58.5 ± 31.2 vs 36.9 ± 29.1, p<0.001). The Rydel-Seiffer tuning fork test has revealed a significant impairment of vibrational sensing on the lower limb in patients (right hallux: 6.8 ± 0.9 vs. 7.4 ± 0.8, p=0.030; left hallux: 6.9 ± 0.8 vs. 7.3 ± 0.9, p=0.029). The Neuropad® testing showed a significant impairment of sudomotor function in women with obesity. A negative correlation was found in patients between BMI and the 25-hydroxy-D3/D2-vitamin levels (r=-0.41, p=0.00126) and a positive correlation between the BMI and resting systolic blood pressure (r=0.26, p=0.0325). Conclusion Peripheral sensory neuronal and sudomotor function impairments were detected in female patients with obesity compared to the controls with normal BMI. Cardiovascular autonomic dysfunction was also revealed by the Valsalva-ratio in these patients, suggesting the presence of parasympathetic dysfunction. The negative correlation between BMI and the 25-hydroxy-D3/D2-vitamin highlights the potential deficiency of vitamin D in the population affected by obesity.